An Integrated Framework for Addressing the Challenges and Strategies of Technology Adoption: A Systematic Review - Omar Ali; Peter A. Murray; Ahmad Al-Ahmad; Luay Tahat (Emerging Science Journal, 2024)
While the rapid growth of information technology (IT) adoption has not lessened, insufficient attention has been directed towards the major themes and sub-themes of IT adoption challenges. Consequently, this study consists of a systematic literature review of the challenges of technology adoption based on a total of 235 peer-reviewed articles from the business and management literature between 2012-2022. Our longitudinal study provides an integrated framework for matching IT challenges to organizational strategies for transforming IT practices and processes. The results of the review broaden scholarly understanding of the importance of strategic IT agility, the need to keep pace with competitive information systems and IT environments. The findings enhance understanding of the pre-change and post-change processes of IT adoption, expanding knowledge on adoption success and organizational strategies for achieving IT strategic agility. Three key contributions include closing gaps not explored in comparative studies, adopting a unified approach with an integrated research model, and strategies to enhance an organization's absorptive IT capacity and agility. Doi: 10.28991/ESJ-2024-08-03-025 Full Text: PDF